Japiim Health: Democratizing Access to Brazilian Arbovirus Data via Retrieval-Augmented Generation on WhatsApp - Gonçalves, Ana Rita Marega; Maia, Nicolas de Souza; Maia, Melissa de Souza; Barreto, Marina Carvalho Arruda; Bonidia, Robson Parmezan; de Carvalho, André (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2026)
Although the “Sistema de Informação de Agravos de Notificação” is fundamental for epidemiological surveillance in Brazil, its complex tabular format and the lack of contextual interpretation in existing visualization tools create significant barriers to data accessibility. In this context, we present Japiim, a multimodal chatbot integrated with WhatsApp, developed to democratize access to national microdata on arboviruses. Based on a Retrieval-Augmented Generation (RAG) architecture and the Sabiá-4 language model, Japiim processes granular health records, transforming them into intuitive texts, voice responses, and dynamic charts. A comparative analysis with general-purpose language models (ChatGPT, Gemini, Claude) reveals that Japiim mitigates quantitative hallucinations and imposes strict safety limits, avoiding the generation of inappropriate medical advice. By combining a widely adopted and low-friction communication platform with a foundation in reliable data, Japiim empowers health managers and citizens with precise and immediate information on public health.